2019
DOI: 10.1002/dev.21915
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress impairs children's sustained attention with increased vulnerability for children of mothers reporting higher parenting stress

Abstract: Despite evidence that acute stress impairs attention in adults, there has been minimal research in children. Here, the effects of acute stress on Go/No-go performance were examined in young children (M age = 5.41 years). Given the critical role of the parent-child relationship to children's self-regulatory development, the extent to which parenting stress predicts children's cognitive vulnerability to acute stress and autonomic reactivity was also investigated. A between-groups design (n = 58 stress, n = 26 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
(105 reference statements)
0
10
0
3
Order By: Relevance
“…Go/No-go task. Children performed a child-friendly version of a zoo-themed Go/No-go task (Grabell et al, 2017;Grammer et al, 2014), adapted to include negative feedback on Go trails and positive or negative feedback on No-go trials (see Roos et al, 2019). First, children were told a short story about animals escaping a zoo.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Go/No-go task. Children performed a child-friendly version of a zoo-themed Go/No-go task (Grabell et al, 2017;Grammer et al, 2014), adapted to include negative feedback on Go trails and positive or negative feedback on No-go trials (see Roos et al, 2019). First, children were told a short story about animals escaping a zoo.…”
Section: Methodsmentioning
confidence: 99%
“…Eighty-four mother-child dyads volunteered to participate through community recruitment in a city in the Pacific Northwest region of the United States. Children (age, M = 5.38 years, SD = .65, range = 4.20 to 6.71 years) were randomly assigned to a Control (n = 26, 14 female) or Stressor condition (n = 58, 33 female), with more children in the Stressor condition to permit examination of within-condition individual differences (see Roos et al, 2019). Pre-enrollment screening excluded children with a history of psychiatric disorders, developmental delays, or serious health problems.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention was found to be impaired in all study participants, whether they had been abused (15), neglected (45,59), exposed to the combination of physical abuse with neglect (55), or exposed to family trauma ( 61). An investigation found that children exposed to an acute stressful experimental event had their sustained attention altered, and the vulnerability of attention increased when they were exposed to parental stress (60).…”
Section: Cognitive and Neuropsychological Alterationsmentioning
confidence: 99%
“…Undoubtedly, recent scholarship examining children's EF in the context of family socioeconomic status has powerfully advanced our understanding of the deleterious impact of poverty on cardiovascular and endocrine health (including increased risk of hypertension, diabetes, etc.). In addition, it has also focused attention on the way stress affects the developing brain (Brito & Noble, ; Hanson et al, ; Roos et al, ). Findings of the costs of poverty to early development have helped us to now recognize the stress associated with material insufficiency as “toxic” in the same ways that we now recognize the impact of airborne pollutants on children's respiratory health (Lupien, McEwen, Gunnar, & Heim, ; Shonkoff, Boyce & McEwen, ).…”
Section: Adaptation Not Deficitmentioning
confidence: 99%